2011
DOI: 10.2174/1874471011104010044
|View full text |Cite
|
Sign up to set email alerts
|

PET Measurements of cAMP-Mediated Phosphodiesterase-4 with (R)-[11C]Rolipram

Abstract: Cyclic adenosine monophosphate (cAMP) is the common second messenger in signal-transduction cascades originating at a number of monoamine receptors involved in neurotransmission, cardiac function and smooth muscle contraction. Altered regulation of cAMP synthesis (at receptors, G-protein subunits or adenylyl cyclase) and breakdown by phosphodiesterase (PDE) enzymes have been implicated in a number of pathologies. The PDE4 inhibitor (R)-rolipram, and the less active (S)- enantiomer, have been labeled with carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Further studies are needed to verify whether these results may be of benefit in human nutrition, for example to help patients with stress disorders. Kenk et al (305) demonstrated via positron emission tomography imaging of cAMP, a strong region-specific signal in the brain, as well as an impaired cAMP-mediated signalling in obese pigs, giving some insight into pathological progression with potential for directing therapy in humans. Kenk et al (305) demonstrated via positron emission tomography imaging of cAMP, a strong region-specific signal in the brain, as well as an impaired cAMP-mediated signalling in obese pigs, giving some insight into pathological progression with potential for directing therapy in humans.…”
Section: Differences Between Pigs and Humans Or Pig Studies With No mentioning
confidence: 99%
“…Further studies are needed to verify whether these results may be of benefit in human nutrition, for example to help patients with stress disorders. Kenk et al (305) demonstrated via positron emission tomography imaging of cAMP, a strong region-specific signal in the brain, as well as an impaired cAMP-mediated signalling in obese pigs, giving some insight into pathological progression with potential for directing therapy in humans. Kenk et al (305) demonstrated via positron emission tomography imaging of cAMP, a strong region-specific signal in the brain, as well as an impaired cAMP-mediated signalling in obese pigs, giving some insight into pathological progression with potential for directing therapy in humans.…”
Section: Differences Between Pigs and Humans Or Pig Studies With No mentioning
confidence: 99%
“…Furthermore, up to our knowledge the only reported PDE PET radioligand that has been evaluated in human subjects is the radiolabeled PDE4 inhibitor [ 11 C]rolipram [36]. Kenk and coworkers have recently reviewed the studies that have been reported so far with [ 11 C]rolipram [37]. However, in view of the fact that PDE4 can also be found in heart, lung and skeletal muscle, PDE4 inhibitors were also evaluated as potential new antiinflammatory drugs [13].…”
Section: Pde4 Pet Radioligandsmentioning
confidence: 99%
“…Since PDE4 enzyme is ubiquitous expressed in brain and no reference region is possible to use for PET purposes, several research studies have been reported exploring the possibility to use the (S)-isomer to define the nonspecific binding component for the (R)analogue [51,53]. Therefore, the difference between those values could be used to calculate the PDE4specific binding of (R)-[ 11 C]rolipram [37]. Therefore, the difference between those values could be used to calculate the PDE4specific binding of (R)-[ 11 C]rolipram [37].…”
Section: Pde4 Pet Radioligandsmentioning
confidence: 99%
“…Numerous other 11 C- and 18 F-labeled PDE10A inhibitors have been evaluated in preclinical rodent models, and although several candidate tracers have proceeded to studies in nonhuman primates and human subjects, the search for a PET tracer with ideal pharmacological properties is ongoing. 2231 …”
Section: Introductionmentioning
confidence: 99%